ANALISIS TAPAK EKOLOGI UNTUK ARAHAN PEMANFAATAN RUANG PULAU LOMBOK - Baiq Ahda Razula Apriyeni; Kukuh Murtilaksono; Setia Hadi (TATALOKA, 2017)
This study aims to 1) Calculate the ecological footprint in Lombok Island through Supply and Demand approach by GFN (Global Footprint Network), Land Suitability and Spatial Planning, 2) Evaluate and assess the three approaches to calculate the value of the ecological footprint, 3) Formulate the direction of spatial use based on the calculation of the ecological footprint. Based on the calculation of the ecological footprint and biocapasity by three approaches found that the results showed Lombok Island was categorized into three categories deficit ecological area: surplus territory (based GFN approach), surplus territory (based on land suitability approach), and deficit area (based on Spatial Planning approach). Of the three approaches of ecological footprint used, Spatial Planning approach was the most realistic to describe the condition of the ecological footprint in Lombok Island. As for the direction of spatial use based on the ecological footprint in Lombok Island was as follows: 1) Agricultural land needs an additional area of 121,305 ha, 2) Farm land area is reduced by 181,031 ha, 3) Fishery land needs an additional area of 248,429 ha, 4) Forest land needs an additional area of 151,439 ha, 5) Developed land needs an additional area of 159,132 ha, and 6) Land which serve as an sequestration needs an additional area of 14,024 ha